Apigenin protects myocardium by inhibiting the TGF-β1-mediated Smad signaling transduction pathway in acute myocardial infarcted rats. (March 2017) - Wang, Ziliang; Chen, Yan; Xu, Dingli
Highlights: Apigenin improves the function and structure of AMI injured cardiomyocytes. Expressions of TGF-β1 and Smad 2 are inhibited by apigenin. Apigenin exerts its effect on cardiomyocytes via TGF-β1/Smad signaling. Abstract: Apigenin is a non-mutagenic flavone that displays both cytostatic and cytoprotective activity. Here, we report results from a preliminary study which explored the mechanism by which apigenin protects myocardium against damage due to acute myocardial infarction (AMI). An AMI model was induced by occluding the left anterior descending (LAD) coronary artery in rats. We then examined the effect of apigenin administration on the function and structure of the AMI-injured heart. Apigenin improved the function and structure of AMI-injured cardiomyocytes, and inhibited TGF-β1 and Smad 2 expression. Although Smad 7 showed a complicated expression pattern, the activity of that indicator was not only induced by AMI induction, but also further augmented by apigenin. Our data conclusively show that apigenin exerts its protective effect by inhibiting TGF-β1, and subsequently modulating the activity of downstream Smads.